Peran Pendidikan Agama Islam dalam Membangun Etika Bermedia Sosial Mahasiswa di Era Transformasi Digital di Universitas Anwar Medika Sidoarjo - Muhammad Syafi’i Anam (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Digital transformation brings massive changes in student communication patterns, but on the other hand, it triggers a crisis of moral degradation such as the spread of hoaxes, cyberbullying, and hate speech. This study aims to analyze the role of Islamic Religious Education (PAI) in guiding and internalizing the values of social media ethics (akhlak al-karimah) among students. Using a descriptive qualitative method based on library research, data were collected from various scientific literature, books, and related journals. The results show that PAI in Higher Education has a strategic role as a moral filter and spiritual guide through contextual-based curriculum reconstruction. The construction of social media ethics from an Islamic perspective relies on the principles of Tabayyun (verification), Qaulan Sadidan (correct words), and Qaulan Ma'rufan (kind words). The actualization of these principles is proven to be able to transform the digital space into a constructive means of education and da'wah.